2005
DOI: 10.1042/bj20051368
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide phosphodiesterases as targets for treatment of haematological malignancies

Abstract: The cAMP signalling pathway has emerged as a key regulator of haematopoietic cell proliferation, differentiation and apoptosis. In parallel, general understanding of the biology of cyclic nucleotide PDEs (phosphodiesterases) has advanced considerably, revealing the remarkable complexity of this enzyme system that regulates the amplitude, kinetics and location of intracellular cAMP-mediated signalling. The development of therapeutic inhibitors of specific PDE gene families has resulted in a growing appreciation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
109
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 288 publications
(321 reference statements)
2
109
0
Order By: Relevance
“…Precise regulation of intracellular cAMP is crucial for this ubiquitous second messenger to control a wide variety of cellular functions, including cell proliferation and differentiation (2), cell metabolism (2), memory formation (5), cardiac contractility (4), and immune responses (1,3). It has been shown that expression of specific isoforms, subcellular localization, and differential regulation of ACs greatly contribute to the diverse and tissue-specific regulation of cAMP (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Precise regulation of intracellular cAMP is crucial for this ubiquitous second messenger to control a wide variety of cellular functions, including cell proliferation and differentiation (2), cell metabolism (2), memory formation (5), cardiac contractility (4), and immune responses (1,3). It has been shown that expression of specific isoforms, subcellular localization, and differential regulation of ACs greatly contribute to the diverse and tissue-specific regulation of cAMP (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the presence of neurotrophin receptors including TrkB has been reported on tumor cells and implicated in malignancy (Desmet and Peeper, 2006). However, cAMP may have anticancer effects, at least in some neoplastic diseases (Chen et al, 1998;Lerner and Epstein, 2006). Therefore, cAMP signaling may be more selective than BDNF/TrkB in protecting normal components of the nervous system without compromising cancer cell killing.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Inhibition of PDE4 by the selective inhibitor rolipram is shown to suppress tumor growth and augments the anti-tumor effects of chemotherapy and radiation therapy in medulloblastoma, glioblastoma 17 and in several hematological malignancies. 18 Why PDE4 isoforms are overexpressed in so many different tumor types remains elusive, but like other tumorigenesis factors, PDE4 isoforms may be regulated by changes in hypoxia. Adaptation to hypoxia is critical for tumor cell growth and 1 survival.…”
Section: Introductionmentioning
confidence: 99%